A copper-doped ZIF-8: a high-performance catalyst for eco-friendly Ullmann and Biginelli reactions - Zahra Doraghi; Heshmatollah Alinezhad; Arezoo Ahmadi (Scientific Reports)
Abstract Metal-organic frameworks (MOFs) with high porosity have gained significant interest in organic reactions. In this study, copper-doped ZIF-8 (Cu-ZIF-8) was synthesized at room temperature, followed by oven drying at 60 °C, and subsequently employed as a highly efficient heterogeneous catalyst for both Ullmann cross-coupling and Biginelli reactions. The catalyst was characterized using various techniques, including FT-IR, XRD, BET, BJH, TGA, EDX, ICP, and SEM. These analyses confirmed that the ZIF-8 preserved its structural integrity after copper incorporation. Cu-ZIF-8 demonstrated remarkable catalytic activity in the Ullmann reaction, achieving a 93% yield with a small catalyst loading of 50 mg. In a similar manner, utilizing ethanol as a green solvent under reflux conditions along with loading 30 mg of the catalyst produced a 90% product yield in the Biginelli reaction. The synthesized products were further verified through melting point determination and NMR spectroscopy.